2004
DOI: 10.1007/bf03218995
|View full text |Cite
|
Sign up to set email alerts
|

PTC behavior of polymer composites containing ionomers upon electron beam irradiation

Abstract: We have prepared polymer composites of low-density polyethylene (LDPE) and ionomers (Surlyn 8940) containing polar segments and metal ions by melt blending with carbon black (CB) as a conductive filler. The resistivity and positive temperature coefficient (PTC) of the ionomer/LDPE/CB composites were investigated with respect to the CB content. The ionomer content has an effect on the resistivity and percolation threshold of the polymer composites; the percolation curve exhibits a plateau at low CB content. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Some authors [13][14][15][16] reported a slower-than-linear decrease of electrical resistance with increasing temperature in conductive filler based polymer composites. However, other authors observed in nano-carbon/polymer composites an increase of electrical resistance with increasing temperature [17,18]. The causes of this apparent inconsistency deserve a closer look.…”
Section: Introductionmentioning
confidence: 84%
“…Some authors [13][14][15][16] reported a slower-than-linear decrease of electrical resistance with increasing temperature in conductive filler based polymer composites. However, other authors observed in nano-carbon/polymer composites an increase of electrical resistance with increasing temperature [17,18]. The causes of this apparent inconsistency deserve a closer look.…”
Section: Introductionmentioning
confidence: 84%
“…This is in good agreement with the SEM results (Figure ). The unique structure of the polar additives with oxygen-containing functional groups suggests that they could act as dispersion agents . This might be enabled by the high loading of CBs (65 wt %) compared to the small traces of polar additives (5 wt %) in the present system, which facilitates the formation of the conductive networks.…”
Section: Resultsmentioning
confidence: 98%
“…The unique structure of the polar additives with oxygen-containing functional groups suggests that they could act as dispersion agents. 48 This might be enabled by the high loading of CBs (65 wt %) compared to the small traces of polar additives (5 wt %) in the present system, which facilitates the formation of the conductive networks. 4d,e, the logarithmic resistivity of the non-irradiated nanocomposites increased with increasing the temperatures and suddenly began to decrease near the melting point of HDPE (∼130 °C), which denoted an NTC effect.…”
Section: Morphology and Crystallizationmentioning
confidence: 97%
See 1 more Smart Citation
“…The composite materials exhibit PTC behavior, effectively serving as current-limiting devices and regulating heating temperatures by adjusting the output energy. 33 Kim et al 34 investigated the variation of the minimum tripping current (I trip) for surlyn/low-density polyethylene (LDPE)/CB composite materials. When a current of 1.2 A is applied, the switching device triggers in approximately 10 s. However, when the current is below 0.7 A, the heat generated by the device and dissipated into the environment reaches an equilibrium state, rendering the PTC effect ineffective.…”
Section: ■ Introductionmentioning
confidence: 99%